Modeling and Simulation of the Process of Natural Gas Fractionation - I. B. Tuychiyev; A. B. Kamolov (International Journal on Orange Technologies, 2021)
In this work, the steady-state model of the process of natural gas fractionation was developed and analyzed using Aspen Plus. Mixture of gases after primary separation was obtained as a selected gas, and this product consists of 68% and 32% of propane and butane, respectively. The optimal reflux ratio and product purity were calculated considering the minimal energy consumption of the reboiler and cooler. The flexibility of the actual column and the change in the number of stages for different types of flowrates were investigated. In addition, optimal feed stage have been found according to overall efficiency for product quality and energy consumption of reboiler and cooler.